The The Increase value of Trash Fish and Sort Fish through Diversification of Processed Fishery Products as an Alternative Businesses to Community in Teluk Nibung District, Tanjungbalai Asahan - Siregar, Erpiani; Manurung, Lucia Dewi Indrayani; Siregar, Rizki Febriansyah; Syahputra, Sofyan Anwar (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Teluk Nibung is one of the sub-districts in Tanjungbalai Asahan City which has fishery potential. This district is also the center of fishery activities. Loading and unloading activities on ships and fish auction places a byproduct in the form of trash fish. From information in the field, it is known that this trash fish is often not used, especially during the big season. Usually used as flour to become animal feed or cat food. The economic value of this fish is very low, ranging from IDR 1000 to IDR 5000. From the survey results, it is known that the condition of this fish is still very fresh in accordance with the provisions of (Indonesian standard of fresh fish) SNI 2729: 2013 fresh fish. As perishable material it is necessary to handle and process it. This activity was carried out in the Lingkungan Kapias Pulau Buaya by inviting partners of housewives. In general, only 10% of housewives in this neighborhood work in the formal sector, therefore processing trash fish into fish drgaon-feet, fish fingers, and shredded fish needs to be done because besides being delicious, it is almost popular with all groups. Methods of this activity include counseling, lectures / discussions, training and hands-on practice. The results of the activities carried out received an enthusiastic welcome from the partners / participants. Active partners ask questions, discuss and participate in direct practice. It is hoped that a follow-up to this activity will form a business unit that will be economically independent.